Exploring the Impact of Remittance Inflows on Investment Patterns: A Case Study of Rupandehi District, Nepal - Gautam, Tara Prasad (International Research Journal of Parroha, 2024)
Remittance inflows have surpassed other sources of foreign currency in many developing countries, with Nepal ranking among the top five recipients relative to its Gross Domestic Product (GDP). This study examines the impact of remittances on investment in Nepal, particularly in the Rupandehi district. With remittances growing at an annual rate of approximately 20%, they significantly influence the Nepalese economy. A survey involving 404 respondents explored how remittance funds are utilized across various sectors, including land purchases, housing reconstruction, share market investments, small business ventures, and electronic appliance acquisitions. The findings reveal that while there is no significant association between remittance amounts and land purchases or housing reconstruction, a significant link exists between remittance amounts and the types of houses purchased or reconstructed. Additionally, no significant association was found between remittance amounts and business investments or the purchase of electronic appliances and internet services. The study also indicated no significant relationship between migrant education and investments in land, housing, or the share market; however, a strong association was noted between the number of migrants and land purchases. These results suggest that while remittances contribute to various investment avenues, their impact varies across different types of investments.